2018
DOI: 10.1016/j.eml.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Techniques to stimulate and interrogate cell–cell adhesion mechanics

Abstract: Cell–cell adhesions maintain the mechanical integrity of multicellular tissues and have recently been found to act as mechanotransducers, translating mechanical cues into biochemical signals. Mechanotransduction studies have primarily focused on focal adhesions, sites of cell-substrate attachment. These studies leverage technical advances in devices and systems interfacing with living cells through cell–extracellular matrix adhesions. As reports of aberrant signal transduction originating from mutations in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 213 publications
(215 reference statements)
0
7
0
Order By: Relevance
“…[116] It has long been thought that DSMs have no role in mechanosensing, but recent studies using FRET-based tension sensors showed that the desmosomal cadherin desmoglein 2 and the plakin protein desmoplakin can bear mechanical tension, thus opening the possibility that DSMs can serve as sites of mechanotransduction. [116,117] By analogy to the role of plectin in force modulation by HDs, desmoplakin in DSMs might initiate mechanosignaling after relief of its auto-inhibited non-canonical SH3 domain by mechanical force [67] and oppose force generation by AJs [118] (Figure 2). Moreover, DSM assembly requires the presence of AJs, [119] again similar to the role of FAs in formation of HDs.…”
Section: Force Distribution Between Cell-extracellular Matrix and Celmentioning
confidence: 99%
“…[116] It has long been thought that DSMs have no role in mechanosensing, but recent studies using FRET-based tension sensors showed that the desmosomal cadherin desmoglein 2 and the plakin protein desmoplakin can bear mechanical tension, thus opening the possibility that DSMs can serve as sites of mechanotransduction. [116,117] By analogy to the role of plectin in force modulation by HDs, desmoplakin in DSMs might initiate mechanosignaling after relief of its auto-inhibited non-canonical SH3 domain by mechanical force [67] and oppose force generation by AJs [118] (Figure 2). Moreover, DSM assembly requires the presence of AJs, [119] again similar to the role of FAs in formation of HDs.…”
Section: Force Distribution Between Cell-extracellular Matrix and Celmentioning
confidence: 99%
“…At the same time, a suspension cell is held by a holding pipette with negative pressure and an injection needle with a positive pressure performing microinjections ( Figure 6 d). Additionally, the movement of the needle during microinjection is shown in Figure 6 e. Various mechanical properties of cells can be measured using this technique, such as investigating membrane elasticity, single-cell mechanotransduction study, molecular adhesion measurements between cell pairs, and quantifying mechanical and material properties of single-cell and cell nuclei [ 55 ]. The MA technique was used by Dufu et al, and they investigated the effect of voxelator (GBT440; anti-polymerization and anti-sickling agent) on the deformability of sickle Red blood cells (SS RBCs).…”
Section: Single-cell Mechanical Properties For Mechanotransductionmentioning
confidence: 99%
“…In recent years, surface sensitive techniques such as quartz crystal microbalance (QCM) or surface plasmon resonance (SPR) have been developed, as well as various passive (including particle displacement, particle deformations due to strain, stress-based FRET sensors, etc.) and active (including atomic force microscopy (AFM) and optical and magnetic tweezers) measurement techniques [13,14]. Of those techniques, AFM offers a unique combination of scale (nm to µm) and force (pN to µN), while enabling measurements in ambient conditions, (bio)chemical modifications of the probe, and combination with optical microscopy [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%